Acute Aerobic Exercise Remodels the Adipose Tissue Progenitor Cell Phenotype in Obese Adults - Ludzki, Alison C.; Krueger, Emily M.; Baldwin, Toree C.; Schleh, Michael W.; Porsche, Cara E.; Ryan, Benjamin J.; Muir, Lindsey A.; Singer, Kanakadurga; Lumeng, Carey N.; Horowitz, Jeffrey F. (Frontiers in Physiology, 2020)
Adipose tissue pathology in obese patients often features impaired adipogenesis, angiogenesis, and chronic low-grade inflammation, all of which are regulated in large part by adipose tissue stromal vascular cells (SVC; i.e. non-adipocyte cells within adipose tissue including preadipocytes, endothelial cells, and immune cells). Exercise is known to increase subcutaneous adipose tissue lipolysis, but the impact of exercise on SVCs in adipose tissue has not been explored. The purpose of this study was to assess the effects of a session of exercise on preadipocyte, endothelial cell, macrophage, and T cell content in human subcutaneous adipose tissue. We collected abdominal subcutaneous adipose tissue samples from ten obese adults (BMI 33±3 kg/m2, body fat 41±7 %) 12h after a 60 min acute session of endurance exercise (80±3 %HRpeak) versus no acute exercise session. SVCs were isolated by collagenase digestion and stained for flow cytometry. We found acute exercise reduced preadipocyte content (38±7 vs. 30±13 %SVC; P=0.04). The reduction was driven by a decrease in CD34hi preadipocytes (18±5 vs. 13±6 %SVC; P=0.002), a subset of preadipocytes that generates high lipolytic rate adipocytes ex vivo. Acute exercise did not alter endothelial cell content. Acute exercise also did not change total immune cell, macrophage, or T cell content, and future work should assess the effects of exercise on subpopulations of these cells. We conclude that exercise may rapidly regulate the subcutaneous adipose tissue pre-adipocyte pool in ways that may help attenuate the high lipolytic rates that are commonly found in obesity.